Respuesta :

Answer:

[tex](\frac{6x^2y}{5})[/tex]

Step-by-step explanation:

Given

[tex]\frac{(2x)(3x^3y^2)}{5x^2y}[/tex]

Required

Solve

Open the brackets

[tex]\frac{(2x)(3x^3y^2)}{5x^2y}[/tex] = [tex]\frac{(2x*3x^3y^2)}{5x^2y}[/tex]

[tex]\frac{(2x)(3x^3y^2)}{5x^2y}[/tex] = [tex]\frac{(6x^4y^2)}{5x^2y}[/tex]

Apply law of indices:

[tex]\frac{(2x)(3x^3y^2)}{5x^2y}[/tex] = [tex]\frac{(6x^{4-2}y^{2-1})}{5}[/tex]

[tex]\frac{(2x)(3x^3y^2)}{5x^2y}[/tex] = [tex]\frac{(6x^2y)}{5}[/tex]

[tex]\frac{(2x)(3x^3y^2)}{5x^2y}[/tex] = [tex](\frac{6x^2y}{5})[/tex]